Resynchronized pregnancyrates in dairy cattle: timingof gonadotropin-releasinghormone injection before timedartificial insemination - C.A. Martel; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2008)
Lactating dairy cows and replacement virgin heifers of unknown pregnancy status were treated with either gonadotropin-releasing hormone (GnRH) or saline to initiate a resynchronization program that was continued 7 days later when a not-pregnant diagnosis was determined. Nonpregnant cattle were administered prostaglandin F2αand then either injected with GnRH 56 hours later and artificially inseminated (AI) by appointment at 72 hours or injected and inseminated concurrently at 72 hours. Injection of GnRH at 56 hours produced more pregnancies than injection of GnRH at 72 hours when AI was administered at 72 hours in both treatments (30.9 vs. 15.2%). Further, starting the resynchronization with GnRH was beneficial to resulting pregnancy rates but was timing dependent. When a not-pregnant status was determined between day 30 and 36 after AI, upfront GnRH injection (7 days before pregnancy diagnosis) may not be necessary because stage of cycle is 1 to 7 days (days 3 to 4 in 71% of cattle) and resulting pregnancy rates after GnRH or saline did not differ (27.5 vs. 26.6 %, respectively). In contrast, when pregnancy status was determined after day 36 (days 37 to 43; cycle days 10 to 11 in 71% of cattle), upfront GnRH as part of the resynchronization protocol nearly doubled the number of pregnancies compared with saline (31.0 vs. 15.1%).; Dairy Day, 2008, Kansas State University, Manhattan, KS, 2008; Dairy Research, 2008 is known as Dairy Day, 2008
Keywords: Dairy Day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-134-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1002; Dairy; Resynchronized pregnancy rate; Gonadotropin-releasing hormone; Artifical insemination